Julius Caesar - "Shakespeare, William" (Penguin Books Ltd London, 1994)
Julius Caesar by William Shakespeare explores power, betrayal, and political ambition in ancient Rome. The play follows the conspiracy to assassinate Caesar, led by Brutus and Cassius, fearing his rise to dictatorship. Caesar$1 (Bs death sparks chaos, manipulated by Mark Antony$1 (Bs stirring funeral speech. Civil war erupts, leading to the downfall of the conspirators. The tragedy highlights the consequences of moral conflict and the fragility of democracy.s
Keywords: Assassination Drama